2014
DOI: 10.1021/bm500224f
|View full text |Cite
|
Sign up to set email alerts
|

Decorin Mimic Regulates Platelet-Derived Growth Factor and Interferon-γ Stimulation of Vascular Smooth Muscle Cells

Abstract: Following balloon injury, smooth muscle cells (SMCs) serve as targets for many of the pro-inflammatory and pro-fibrotic factors, including platelet-derived growth factor (PDGF) and interferon-γ (IFN-γ) released from activated inflammatory cells and platelets. Previously, our lab designed a mimic of the proteoglycan decorin, termed DS-SILY20, that suppressed vascular SMC proliferation, migration, and protein synthesis in vitro, and injured vessels treated with DS-SILY20 demonstrated reduced hyperplasia in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 65 publications
1
22
1
Order By: Relevance
“…The binding to type I, type VI collagen and fibronectin affects collagen fibril formation and modulates the ECM rigidity and stiffness, structural properties known to influence angiogenesis [159,160,161]. As other ECM molecule, decorin modulates the activity of pro-angiogenic growth factors including VEGF, PDGF, FGF, Insulin Growth Factor (IGF) and angiopoietin by sequestering them and influencing their availability [162,163,164,165]. Decorin controls also the bioavailability of TGF-β whose release depends on the activity of different proteases involved in angiogenesis [166,167].…”
Section: Proteoglycans: Complex Functions From the Protein Core Anmentioning
confidence: 99%
“…The binding to type I, type VI collagen and fibronectin affects collagen fibril formation and modulates the ECM rigidity and stiffness, structural properties known to influence angiogenesis [159,160,161]. As other ECM molecule, decorin modulates the activity of pro-angiogenic growth factors including VEGF, PDGF, FGF, Insulin Growth Factor (IGF) and angiopoietin by sequestering them and influencing their availability [162,163,164,165]. Decorin controls also the bioavailability of TGF-β whose release depends on the activity of different proteases involved in angiogenesis [166,167].…”
Section: Proteoglycans: Complex Functions From the Protein Core Anmentioning
confidence: 99%
“…In addition to VEGF and TGF-β, decorin interacts with several other angiogenic growth factors, including platelet-derived growth factor (PDGF) [123,142,143], fibroblast growth factor (FGF) [93,144], insulin-like growth factor (IGF) [120,121,145], connective tissue growth factor (CTGF) [146148], and HGF [118,149]. Furthermore, decorin influences the availability of the proangiogenic factor angiopoietin, as well [94].…”
Section: Potential Mechanism(s) For Decorin In Angiogenesismentioning
confidence: 99%
“…Cytotoxins currently utilized to minimize maladaptive cell behaviour following PCI are non‐selective, and the goal for functional vascular healing should be a development of new active ingredients that promote EC growth while inhibiting unregulated SMC behaviour. Previously, we have demonstrated that DS–SILY 20 modulates SMC migration, protein synthesis, cytokine secretion and vascular injury marker production in both proliferative and quiescent SMCs (Scott et al ., ; Scott and Panitch, ). Conversely, in this study, we reveal that DS–SILY 20 supports EC proliferation and migration in vitro (Figure B, C).…”
Section: Discussionmentioning
confidence: 99%